(untitled) (Research, Society and Development, 2021)
This article presents results acquired through studies carried out on the practices of continuing education for teachers today, which is the main focus. This work focused on showing aspects of the training proposals, and also reflecting on the significant importance of continuing education and the daily practices of Basic Education educators. The methodology presented here is based on qualitative research. It also presents strategies on how educators can work on curriculum content through technologies and games. It is clear that in their initial training, educators do not hold all the knowledge that is necessary to meet all the needs that students bring to a classroom today, as the context of the student’s life changes according to each reality, and with this, it is necessary that today’s educators continue to study and update themselves, carrying out quality continuing education in order to (re)learn, or (re)signify their daily practices, seeking to improve their knowledge and practices in your everyday experiences.